Sustainable Budget and the Sustainability Appearing in the Budget - Domokos, László; Pulay, Gyula (Public Finance Quarterly, 2020)
Fiscal sustainability has become one of the most important requirements of fiscal policy over the past two to three decades. Hungary’s Fundamental Law stipulates that Hungary enforces the principle of sustainable budget management. In international practice, fiscal sustainability is often identified with preserving the solvency of the state and the sustainable financing of public debt. The risks related to the fulfilment of the constitutional requirement to reduce public indebtedness are also regularly assessed by the State Audit Office, for which it has developed its own risk analysis method. The authors of the article define fiscal sustainability as a series of budgets that provide coverage for the public goods needs of present generations while increasing the capacity and opportunity of future generations to meet their own future needs. Based on this, and building on the resolution of the National Assembly and international good practices, they present how the coverage of Sustainable Development Goals can be integrated into the respective budgets in a transparent and accountable way.